Model Sistem Penelusuran Alumni SMP Negeri 5 Loli Berbasis Teknologi - ersita dama nuna; Yulius Nahak Tetik; Alexander Adis (Journal Of Informatics And Busisnes, 2024)
One of the junior high schools in West Sumba is SMP N 5 Loli. The study period here lasts for 3 years, like other schools in Indonesia. Based on findings from interviews conducted at SMPN 5 Loli, alumni tracing will be done by sending letters to students to answer questions with their signatures. Tracking or tracing alumni is one of the methods used by some schools in Indonesia to get answers from their graduates. The answers obtained from the graduates are very important for the school in their efforts to improve and enhance the quality and education system. Therefore, an internet-based system will be developed that allows alumni to access information via the internet using mobile phones, gadgets, laptops, or other devices according to their wishes and needs. The system also has the ability to store existing alumni search data and automatically generate reports containing the percentage of alumni responses so that administrators can compile alumni search reports without having to re-enter or move the search data to another system. The method used by the author in modeling this system is waterfall. Waterfall is one of the simple system development methods consisting of 5 stages: software requirements analysis, system design, system implementation, testing, and maintenance. The system testing used in the research on modeling this system is Black Box. Based on the research results and discussion, it can be concluded that this research produces a model of the alumni tracer study system and the system can display alumni data based on the year of the alumni batch.